Africa South of the Sahara. - Europa Publications Limited (London, Europa Publications Ltd., 1971)
Vols. for 1971- include a section entitled "Who's who in Africa South of the Sahara."
Published by: Routledge, <2007->
Vols. for <1973-> called also <3rd. ed.->; <1976/1977-1984/1985>called also <6th-14th ed.>; 1986- called also 15th ed.-
Keywords: 2; Organisation administrative; Annuaires; 2; 2; 2; economic conditions; social situation; demography; geography; history; imperialism; financial market; international organisation; statistics; agricultural situation; trading operation; industrial structures; organisation of transport; Southern Africa; Angola; Botswana; Ethiopia; Chad; Kenya; Lesotho; Liberia; Malawi; Nigeria; South Africa; Democratic Republic of the Congo; Zimbabwe; 2; situation sociale; 2; 2; histoire; 2; 2; organisation internationale; statistique; situation de l'agriculture.; 2; structure industrielle; organisation des transports; 2; Angola; Botswana; 2; Tchad; Kenya; Lesotho; Liberia; Malawi; Nigeria; Afrique du Sud; 2; Zimbabwe; Africa, Sub-Saharan -- Periodicals; Africa, Central